If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = n + 5 + -2 Reorder the terms: 3 = 5 + -2 + n Combine like terms: 5 + -2 = 3 3 = 3 + n Add '-3' to each side of the equation. 3 + -3 = 3 + -3 + n Combine like terms: 3 + -3 = 0 0 = 3 + -3 + n Combine like terms: 3 + -3 = 0 0 = 0 + n 0 = n Solving 0 = n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 0 + -1n = n + -1n Remove the zero: -1n = n + -1n Combine like terms: n + -1n = 0 -1n = 0 Divide each side by '-1'. n = 0 Simplifying n = 0
| 2y-y=20 | | log(x^2-4)=8 | | 14w-10w=20 | | x+3.2*4=223 | | 4x+10+3x-11=90 | | 13h-3h=20 | | 3(a+6)=39 | | (5x-6y)+(6x-5y)= | | 13.54m/4 | | -8(a-3)=-8a+25 | | 4x+10+3z-11=90 | | 2x-1+2x-1+4x+8=112 | | 2v-v=10 | | (3y+2)(5y^2+4y-3)= | | (5x-6y)(6x-5y)= | | 84/x=7 | | t/14=49/35 | | 9x+6+6x-6=90 | | 2x-4=10x-17 | | x^4-4x^3-8=0 | | 3s+5t=8 | | 600+468+870= | | 7-8=9(x-12) | | 110-x=3x+10 | | 15xsquared+9x=0 | | x^2+8-8=0 | | 3(x+4)=5x+6 | | 8x^4+10x^3+9x^2+x-1=0 | | 7x-10=3x+26 | | 10x-6 = 114 | | 1+2n-3=74 | | 15x+77=77 |